2018
DOI: 10.5194/bg-15-6329-2018
|View full text |Cite
|
Sign up to set email alerts
|

Vivianite formation in methane-rich deep-sea sediments from the South China Sea

Abstract: Abstract. Phosphorus is often invoked as the ultimate limiting nutrient, modulating primary productivity on geological timescales. Consequently, along with nitrogen, phosphorus bioavailability exerts a fundamental control on organic carbon production, linking all the biogeochemical cycles across the Earth system. Unlike nitrogen that can be microbially fixed from an essentially infinite atmospheric reservoir, phosphorus availability is dictated by the interplay between its sources and sinks. While authigenic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 114 publications
(224 reference statements)
0
22
0
Order By: Relevance
“…The slope of the northern SCS is one of the world's most active areas of modern marine sedimentary processes (Huang and Wang, 2007;Luan et al, 2019). A large amount of river-borne terrigenous sediment input leads to exceptionally high amount of iron oxides in the sediments of the northern SCS (Zhang et al, 2007;Liu Z. F. et al, 2016;Liu et al, 2018). Previous research had suggested that different kinds of iron oxides could serve as electron acceptors for Fe-AOM (Bar-Or et al, 2017).…”
Section: Iron-mediated Anaerobic Oxidation Of Methanementioning
confidence: 99%
See 1 more Smart Citation
“…The slope of the northern SCS is one of the world's most active areas of modern marine sedimentary processes (Huang and Wang, 2007;Luan et al, 2019). A large amount of river-borne terrigenous sediment input leads to exceptionally high amount of iron oxides in the sediments of the northern SCS (Zhang et al, 2007;Liu Z. F. et al, 2016;Liu et al, 2018). Previous research had suggested that different kinds of iron oxides could serve as electron acceptors for Fe-AOM (Bar-Or et al, 2017).…”
Section: Iron-mediated Anaerobic Oxidation Of Methanementioning
confidence: 99%
“…The Jiaolong and Haima methane seeps are the two still-active seep sites in SCS. Previous studies on the seeps in SCS have led to many significant advancements including new insight into the methane seep structure ( Liu et al, 2018 ), mineral carbon/oxygen/sulfur isotopes ( Feng et al, 2018 ), macrobenthos ( Dong and Li, 2015 ; Gong et al, 2015 ), and microbial lipid biomarkers ( Guan et al, 2016 , 2018 ). In addition, the microbial distribution and diversity in SCS methane seeps were also investigated ( Jiang et al, 2007 ; Zhang et al, 2012 ), and a 16S rRNA gene-based survey indicated the presence of SRB and ANME.…”
Section: Introductionmentioning
confidence: 99%
“…challenged. In this zone only paramagnetic minerals as siderite (FeCO 3 ) and vivianite [Fe(II) 3 (PO 4 )•8H 2 O] were assumed to precipitate under elevated concentrations of dissolved ferrousiron, if pore waters are saturated with respect to carbonate or phosphate, respectively (Berner, 1980;Slomp et al, 2013;Liu et al, 2018). However, several studies have suggested magnetic modification and mineral precipitation just below the SMTZ, mainly monosulfides, pyrrhotite, greigite and pyrite (Dekkers, 1989;Peters and Dekkers, 2003;Riedinger et al, 2005Riedinger et al, , 2014Horng and Chen, 2006;Larrasoaña et al, 2007;Kars and Kodama, 2015;Shi et al, 2017;Horng, 2018;Roberts et al, 2018;Badesab et al, 2019).…”
Section: Diagenetic Processes In the Methanic Zone And Their Impact Omentioning
confidence: 99%
“…A low CRS content was observed only at Unit IV, which is coincidence with the average low TOC/TS ratio in this Unit. However, Liu et al [49] demonstrated that the main biogeochemical processes in Unit IV is controlled by iron mediated anaerobic oxidation of methane (Fe–AOM), which further confirms that of methane rich fluids are well developed in this site.…”
Section: Discussionmentioning
confidence: 52%
“…In fact, Unit III sediments revealed highly 13 C-depleted (extremely negative values) authigenic carbonates, which indicated AOM–SR. On the other hand Unit IV had relatively 13 C-depleted (−4.3‰) authigenic carbonates and was sulfate-poor due to iron–AOM, as demonstrated by Liu [49]. Nevertheless, the sulfate concentrations and δ 13 C TIC values may allow recognition of organoclastic sulfate reduction (OSR) in Unit I where the minimum δ 13 C TIC value was −2‰.…”
Section: Discussionmentioning
confidence: 97%